Measurement Invariance of the GAD-7 and CESD-R-10 Among Adolescents in Canada. (13th November 2021) - Romano, Isabella; Ferro, Mark A; Patte, Karen A; Leatherdale, Scott T
Abstract: Objective: The primary objective of our study was to assess measurement invariance (by grade and sex) of the 7-item Generalized Anxiety Disorder (GAD-7) and 10-item Center for Epidemiologic Studies Depression Revised (CESD-R-10) scales in a sample of adolescents in Canada. If measurement invariance was demonstrated, our secondary objective was to estimate differences in scale scores across these subgroups. Methods: We used data from 59, 052 adolescents in Year 7 (2018–19) of the COMPASS school-based study. Measurement invariance was tested within a multigroup confirmatory factor analysis framework. Differences in scale scores were estimated using mixed linear regression which accounted for school-level clustering and adjusted for relevant confounders. Results: Both the GAD-7 and CESD-R-10 demonstrated strict measurement invariance by sex and grade in our sample. Mean scale scores were higher among adolescents in grade 12 compared to grade 9 (βGAD-7 = 0.91, p  < .001; βCESD-R-10 = 0.99, p  < .001) and among female adolescents compared to males (βGAD-7 = 3.36, p  < .001; βCESD-R-10 = 2.58, p  < .001). Conclusions: Findings support the validity of the GAD-7 and CESD-R-10 for screening risk of generalized anxiety and depression among Canadian adolescents, and further indicate that differences observed in scale scores across subgroups reflect actual differences in risk for generalized anxiety and major depression, respectively.